If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 = 5(x + 3) + 8x Reorder the terms: 2 = 5(3 + x) + 8x 2 = (3 * 5 + x * 5) + 8x 2 = (15 + 5x) + 8x Combine like terms: 5x + 8x = 13x 2 = 15 + 13x Solving 2 = 15 + 13x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13x' to each side of the equation. 2 + -13x = 15 + 13x + -13x Combine like terms: 13x + -13x = 0 2 + -13x = 15 + 0 2 + -13x = 15 Add '-2' to each side of the equation. 2 + -2 + -13x = 15 + -2 Combine like terms: 2 + -2 = 0 0 + -13x = 15 + -2 -13x = 15 + -2 Combine like terms: 15 + -2 = 13 -13x = 13 Divide each side by '-13'. x = -1 Simplifying x = -1
| 18xy=(3x^2) | | 1=3x-1 | | 2(v-7)-4v=4 | | 24x^3-14x^2-x+1=0 | | 35/8= | | 6u^2+13u+5=0 | | 2=-3x+8 | | 49=9y-68 | | 6xy=3x^2 | | y=-3(3)+8 | | 6x+42=2x-2 | | 2y-3+5y=y+15 | | 3x+6y=45 | | 2,295=-74t | | 7y+8(y+6)= | | 3*x+6=5*x | | 8c-4=2-4c | | (x+2)(2x+1)=(x+6)(2x+3) | | 18w=234 | | -27=-7w+4(w-6) | | 4y^2-8y+9=0 | | 14-(5x-6)=-6(x+1)-5 | | (x+1)(x-3)=4 | | [x]=7 | | 4(2x+3)=6(x+3) | | 8=2v+6 | | .5(1-2.5y)+1.25y=.5 | | -17=n/4-13 | | .8(3v-2w)+.2(7v-2w)= | | 3y=7+5 | | -9y-3=-8y-7 | | 11x+8=4x-6 |